2022
DOI: 10.1099/ijsem.0.005191
|View full text |Cite
|
Sign up to set email alerts
|

Wickerhamiella nakhonpathomensis f.a. sp. nov., a novel ascomycetous yeast species isolated from a mushroom and a flower in Thailand

Abstract: Strains SU22T (TBRC 14875T) and FLA11.5, representing a novel anamorphic yeast species, were respectively isolated from a fruiting body of a Coprinus species and an inflorescence of a Coffea species collected in Thailand. Analysis of the sequences of the D1/D2 domains of the large subunit (LSU) rRNA gene and the internal transcribed spacer (ITS) regions showed that the two strains differed by two nucleotide substitutions in the D1/D2 domains of the LSU rRNA gene and were identical in the ITS regions. Wickerham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Approximately 1 g of the tea flower sample was homogenized in 10 mL of sterile 0.85% NaCl as a diluent using a Masticator ® homogenizer blender (Barcelona, Spain) for 5 min. After that, the homogenate was serially diluted to 10 0 –10 5 with the diluent, and 0.1 mL of each dilution was plated on yeast–malt extract agar (YMA) (1% yeast extract, 2% peptone, 2% glucose, and 1.5% agar) supplemented with 100 mg/L of chloramphenicol and then incubated at 30°C for 48 h. Yeast colonies with distinct morphologies were isolated and streaked on the same medium without the supplementation of chloramphenicol for purification ( Khunnamwong et al, 2022 ). For storage, a single colony of each yeast isolate was inoculated in yeast–malt extract broth (YMB) (1% yeast extract, 2% peptone, and 2% glucose) and incubated at 30°C on a 150-rpm rotary shaker for 24 h. The culture was mixed with 30% (v/v) glycerol to make a final concentration of 15% before being stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 1 g of the tea flower sample was homogenized in 10 mL of sterile 0.85% NaCl as a diluent using a Masticator ® homogenizer blender (Barcelona, Spain) for 5 min. After that, the homogenate was serially diluted to 10 0 –10 5 with the diluent, and 0.1 mL of each dilution was plated on yeast–malt extract agar (YMA) (1% yeast extract, 2% peptone, 2% glucose, and 1.5% agar) supplemented with 100 mg/L of chloramphenicol and then incubated at 30°C for 48 h. Yeast colonies with distinct morphologies were isolated and streaked on the same medium without the supplementation of chloramphenicol for purification ( Khunnamwong et al, 2022 ). For storage, a single colony of each yeast isolate was inoculated in yeast–malt extract broth (YMB) (1% yeast extract, 2% peptone, and 2% glucose) and incubated at 30°C on a 150-rpm rotary shaker for 24 h. The culture was mixed with 30% (v/v) glycerol to make a final concentration of 15% before being stored at −80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Two phylogenetic trees based on the sequence of D1/D2 domain derived from ML and NJ analyses showed that the two strains, NBRC 115686 T and NBRC 115687, formed a subclade with W. galacta in the Wickerhamiella clade but in a distinct position from the other Wickerhamiella species in this subclade, with high bootstrap support ( and S1, available in the online version of this article). NBRC 115686 T varies from previously known species of the clade by roughly 12 % in the D1/D2 domains, indicating a significant degree of sequence divergence sufficient to differentiate them at the species level [4, 5, 7, 15–17]. These results suggest the presence of multiple unknown species yet to be discovered.…”
Section: Novel Species Identification and Delineationmentioning
confidence: 97%
“…The Wickerhamiella species is highly specialized nutritionally [8]. Commonly, Wickerhamiella species are able to assimilate d -glucose and l -sorbose but not inulin, raffinose, melibiose, lactose, trehalose, maltose, melezitose, soluble starch, cellobiose, d -salicin, l -rhamnose, l -arabinose, d -ribose, methanol, erythritol, galactitol, myo -inositol, citrate or N -acetyl- d -glucosamine [5]. In this study, the novel species we isolated can be distinguished from the most closely related Wickerhamiella species through phenotypic characteristics.…”
Section: Novel Species Identification and Delineationmentioning
confidence: 99%
See 2 more Smart Citations